Adolescent Self-Compassion Moderates the Relationship between Perceived Stress and Internalizing Symptoms - Kaur, Ms. Kanwaljit (The journal of contemporary issues in business and government, 2019)
Students have often associated high-level assessments with stress, fear and confusion, mainly for two reasons — firstly, the approach to board exams, which leads to pressure to do well academically to ensure admission to higher education. Second, because of the inevitable decision to choose a career path that may determine their destiny. During such stressful times, the ability to look out for one’s own interests and to care for oneself is expected to play a significant role in determining one’s well-being. Gilbert (2005) suggests that self-pity improves well-being because it helps people to feel cared for, connected, and emotionally empathetic. Compassion involves caring for oneself and empathy when faced with perceived difficulties or failures (KornWeld, 1993); Hanh, 1997; Salzberg, 1997; Bennett-Goleman, 2001; Brach, 2003). Therefore, it would be interesting to find out if students who get high marks in self-pity are actually able to cope better with stress and are higher in job aspirations. This study also looked at examining the differences in self-pity, perceived stress and job aspirations among 12th graders. A sample of 120 students, 60 scientists and 60 humanities, (including 30 men and 30 women from each faculty.), Was taken and the differences between the two groups were analyzed using a t-test. The difference is seen in the light of gender and intellect - science and humanity, in the context of current research. The results of the study suggested that empathy is closely related to perceived stress and is closely related to educational aspirations. The effects and impacts were also discussed in detail.